Dynamics of the Macular Hole-Silicone Oil Tamponade Interface with Patient Positioning as Imaged by Spectral Domain Optical Coherence Tomography - Oster, Stephen F. (2010)
PURPOSE: To evaluate with spectral domain optical coherence tomography (SD-OCT) the relationship between the retina and overlying silicone oil tamponade after macular hole surgery, and to evaluate how this relationship changes with patient positioning. PATIENTS AND METHODS: Retrospective consecutive case series of 10 eyes from 9 patients who underwent macular hole surgery with silicone oil tamponade and subsequent SD-OCT scans. Four of the included eyes were also imaged with patients in face-down posture to determine if the silicone-retina apposition changes with prone positioning. Finally, a single patient was additionally scanned in the lateral and supine positions. RESULTS: The posterior surface of the silicone oil bubble was well visualized in all 10 eyes. In the majority of eyes (7/10) the oil tamponade bridged across the macular hole creating a pre-foveal fluid space, but in 3 eyes the silicone oil filled the macular hole and was seen in touch with the underlying foveal depression or retinal pigment epithelium. In 75% of eyes (3/4) the silicone oil-retinal approximation did not vary with face-down position. Supine positioning clearly floated the silicone tamponade anteriorly and off of the retinal surface. CONCLUSIONS: Silicone oil tamponade can either bridge across macular holes, or in a novel finding, can fill the underlying foveal depression or macular hole space. Generally, the oil position is stable between face-forward and prone SD-OCT images, suggesting that either of these patient positions allows waterproofing of the underlying macular hole. Finally, our images confirm that supine positioning should be avoided post-operatively as it leads to loss of oil-retinal tamponade.